PERAN PERPUSTAKAAN DALAM MENINGKATKAN KESEHATAN MENTAL: MENJADI RUANG REFLEKSI DAN REKREASI - As-Syauqi, Rahmat Fajri (UIN Imam Bonjol Padang, 2024)
Libraries have great potential in supporting improved mental health. This study focuses on the importance of social spaces such as libraries which can help individuals face emotional and psychological challenges. The aim of this article is to explore the role of libraries as spaces for reflection and recreation that can reduce stress and improve mental well-being. This research uses a qualitative approach by analyzing various references that focus on mental health. The library method in this research was used to analyze various relevant references regarding the role of libraries in improving mental health. The research results show that libraries that provide a calm atmosphere and various activities can help individuals to self-reflect and gain knowledge that is useful for managing mental health. Libraries also function as a positive escape from the stresses of everyday life. The conclusion of this article is that libraries not only act as information centers, but also as important spaces in supporting the mental and emotional well-being of their visitors. With proper management, libraries can become places that support mental recovery in society.